n+(n+1)+(n+2)+(n+3)=-122

Simple and best practice solution for n+(n+1)+(n+2)+(n+3)=-122 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+(n+1)+(n+2)+(n+3)=-122 equation:


Simplifying
n + (n + 1) + (n + 2) + (n + 3) = -122

Reorder the terms:
n + (1 + n) + (n + 2) + (n + 3) = -122

Remove parenthesis around (1 + n)
n + 1 + n + (n + 2) + (n + 3) = -122

Reorder the terms:
n + 1 + n + (2 + n) + (n + 3) = -122

Remove parenthesis around (2 + n)
n + 1 + n + 2 + n + (n + 3) = -122

Reorder the terms:
n + 1 + n + 2 + n + (3 + n) = -122

Remove parenthesis around (3 + n)
n + 1 + n + 2 + n + 3 + n = -122

Reorder the terms:
1 + 2 + 3 + n + n + n + n = -122

Combine like terms: 1 + 2 = 3
3 + 3 + n + n + n + n = -122

Combine like terms: 3 + 3 = 6
6 + n + n + n + n = -122

Combine like terms: n + n = 2n
6 + 2n + n + n = -122

Combine like terms: 2n + n = 3n
6 + 3n + n = -122

Combine like terms: 3n + n = 4n
6 + 4n = -122

Solving
6 + 4n = -122

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 4n = -122 + -6

Combine like terms: 6 + -6 = 0
0 + 4n = -122 + -6
4n = -122 + -6

Combine like terms: -122 + -6 = -128
4n = -128

Divide each side by '4'.
n = -32

Simplifying
n = -32

See similar equations:

| 7(x+5)-4=33-6x-2+13x | | 160+.40x=293.60 | | 4t-11=-1 | | 1.99s+(2.99*2s)+.15=40 | | 15-2(x+5)=25 | | 2+2+x=6 | | 2r-3=18 | | 11+2g=2g-(g-15) | | 3x+5=5y-8 | | w-1=5w+3w-8 | | 7p+11=3p | | 3+d=9-d | | 2(x+4)+(5x)=7(x+4)-5 | | 4c-3=17 | | 15-3.7m=12.84-2.5m | | -9(3y-4)=-531 | | 5(a-1)=2a+4(a-1) | | 5x+8(x+1)+3=11-3x | | 2(7h-3)=120 | | 4-4(x-3)=20 | | 8-5=11 | | -(1-x)=2(3x-1) | | 9y-6+y=-(y+5y) | | 7r+11r=725-7r | | 5(b+1)=5b+1 | | -25=7+4x | | 5(2x-31)+3=10x-155 | | 6(x-8)-3x=5(x-1)-1 | | 3+5-6+2x=-4(x-3)+7 | | -9(4x-2)=108-6x | | 4(2x+2)=7x+1 | | 6x+3x-x=96 |

Equations solver categories